The Role of Green Accounting Practices in Enhanching Corporate Financial Sustainability - Suwandi Ng (DINASTI RESEARCH, 2026)
This study examines the role of green accounting practices in enhancing corporate financial sustainability. The increasing global emphasis on environmental responsibility, ESG investment frameworks, and regulatory pressures has encouraged firms to integrate environmental considerations into their accounting systems. Despite this development, empirical findings regarding the financial implications of green accounting remain inconsistent and context-dependent. Therefore, this research aims to synthesize existing evidence to clarify how green accounting contributes to long-term financial sustainability. This study employs a structured literature review method by analyzing peer-reviewed journal articles published between 2000 and 2024. Relevant studies were identified through major academic databases using predefined keywords related to green accounting and financial sustainability. After applying inclusion and exclusion criteria, selected articles were systematically examined using thematic content analysis to identify dominant theoretical perspectives, types of green accounting practices, financial indicators, and empirical outcomes. The findings indicate that green accounting practices including environmental cost accounting, carbon accounting, sustainability reporting, and ESG disclosure are positively associated with corporate financial sustainability in most studies. The relationship is primarily mediated through improved operational efficiency, enhanced risk management, stronger stakeholder trust, and better access to capital markets. Although short-term implementation costs may occur, long-term financial benefits tend to outweigh initial expenditures. The study concludes that green accounting functions as a strategic financial management instrument rather than merely a compliance mechanism, contributing significantly to corporate resilience and sustainable financial performance.